The Effect of Service Coverage and Water Loss Rate on the Performance of Tirta Giri Nata - Naufal, Ahmad; Silitonga, Roland Y.H.; Heryanto, Dhany (The Indonesian Institute of Science and Technology Research, 2025)
The performance of the Regional Public Drinking Water Company is an essential indicator in ensuring public access to efficient and sustainable clean water services. This study aims to analyze the influence of service coverage and the rate of water loss (Non-Revenue Water/ NRW) on the performance of Tirta Giri Nata Cirebon City, Indonesia. The approach is quantitative with multiple linear regression methods, based on monthly data from 2021 to 2023. The results showed that the coverage of services had a significant positive effect on performance, while NRW had a significant adverse impact. The determination coefficient (R²) value of 42.1% indicates that both variables explain a large proportion of variations in company performance. These findings affirm the importance of strategies to expand the coverage and control of NRW as a crucial step in improving regional drinking water services' operational efficiency and sustainability.